2016
DOI: 10.1364/ao.55.006243
|View full text |Cite
|
Sign up to set email alerts
|

Temperature drift modeling and compensation of fiber optical gyroscope based on improved support vector machine and particle swarm optimization algorithms

Abstract: Modeling and compensation of temperature drift is an important method for improving the precision of fiber-optic gyroscopes (FOGs). In this paper, a new method of modeling and compensation for FOGs based on improved particle swarm optimization (PSO) and support vector machine (SVM) algorithms is proposed. The convergence speed and reliability of PSO are improved by introducing a dynamic inertia factor. The regression accuracy of SVM is improved by introducing a combined kernel function with four parameters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In the literature, very limited work has been done to show the effectiveness of ML techniques for temperature drift compensation in sensors . In this paper, we proposed to apply different supervised machine learning techniques to learn the characteristics of the temperature drift in ISFET pH sensor based on the collected experimental data.…”
Section: Isfet Temperature Drift Compensation Using ML Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, very limited work has been done to show the effectiveness of ML techniques for temperature drift compensation in sensors . In this paper, we proposed to apply different supervised machine learning techniques to learn the characteristics of the temperature drift in ISFET pH sensor based on the collected experimental data.…”
Section: Isfet Temperature Drift Compensation Using ML Techniquesmentioning
confidence: 99%
“…In the literature, very limited work has been done to show the effectiveness of ML techniques for temperature drift compensation in sensors. [48][49][50][51][52][53] In this paper, we proposed to apply different supervised machine learning techniques to learn the characteristics of the temperature drift in ISFET pH sensor based on the collected experimental data. For the purpose of our experiments, we use the following ML techniques: multi-layer perceptron (MLP, a neural network model), decision trees (DT), polynomial regression (PR, a special case of linear regression), random forests (RF), and support Vector Regression (SVR, Support Vector Machine used for Regression analysis).…”
Section: Isfet Temperature Drift Compensation Using ML Techniquesmentioning
confidence: 99%
“…erefore, some researchers have introduced some optimization algorithms to tackle the limitations. e genetic algorithm (GA) was applied by Pan et al [15], the artificial fish swarm algorithm was applied by Song et al [16], and the particle swarm optimization (PSO) was applied by Wang, Cheng, and Tong et al [17][18][19]. e experimental results indicated that the optimized models are effective and can improve the system's performance.…”
Section: Introductionmentioning
confidence: 99%
“…Golikov et al [13] proposed a new method to compensate the multiplicative and additive errors caused by temperature changes. Wang et al [14] presented a new method to compensate the error and improved the precision of Fiber-Optic Gyroscopes (FOGs) based on improved Particle Swarm Optimization (PSO) and Support Vector Machine (SVM) algorithms. The regression accuracy of the proposed method increased by 83.81% compared with the traditional SVM.…”
Section: Introductionmentioning
confidence: 99%
“…Golikov et al [13] proposed a new method to compensate the multiplicative and additive errors caused by temperature changes. Wang et al [14] presented a new method to compensate the error and improved the precision of Fiber-Optic Gyroscopes (FOGs) based on improved Particle Swarm Optimization (PSO)…”
Section: Introductionmentioning
confidence: 99%